SUSTAINABLE LIVELIHOODS FOR SUKU ANAK DALAM: INTEGRATING LOCAL WISDOM AND NATURAL RESOURCES - Muchlis, Fuad; Elwamendri, Elwamendri; Sardi, Idris; Fathoni, Zakky; Jamil, Ahmad Syariful (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
The issue of poverty and food and nutritional vulnerability in the Suku Anak Dalam (SAD) community in Bukit Duabelas National Park requires special attention. This study will integrate various assets owned by indigenous communities, including local wisdom and social capital, with opportunities to develop the potential of natural resources in TNBD to support the achievement of SDGs. This research aims to describe the picture of SAD livelihoods and their changes and design a design or pattern for sustainable SAD livelihood development. The research uses a constructivist paradigm with a case study approach. Data analysis uses the Sustainable Livelihoods Framework to identify and evaluate SAD individuals or communities' assets, capacities, and strategies for maintaining sustainable livelihoods. The results of this research show that, SAD communities in TNBD still depend on extractive agriculture, such as hunting and gathering, but are starting to switch to plantation cultivation, such as oil palm and rubber. Professions outside the agricultural sector are limited, and their access to formal employment is hampered by limited education and skills. SAD has a variety of assets, including human, natural, social, financial, and physical capital. Social and natural capital are their main assets. Despite limited education, their natural resources are sufficient to support life. To increase SAD's livelihood sources, interventions such as utilizing mapped site space, piloting productive site projects, strengthening cooperation between government, NGOs and the private sector, and community-based sustainable forest management are needed.